STATUS AND ETIOLOGY OF POTATO DRY ROT IN PUNJAB - Kumar, Sanjay (Potato Journal, 2017)
Tubers collected from different cold stores of Punjab were analyzed for the presence of dry rot infection and on subsequent isolations made from infected samples yielded twenty four isolates (F1 to F24) of Fusarium spp. They were identified on the basis of morphological and cultural characters and confirmation of the species was also done by primers specific for four different Fusarium spp. (F. coeruleum, F. sulphureum, F. culmorum and F. avenaceum) known to be associated with dry rot of potato. On the basis of morphological, cultural characters and PCR results F1 - F11 isolates were identified as Fusarium avenaceum; whereas F16, F18 to F24 isolates were identified as Fusarium culmorum. The amplicons of 294 and 592 bp were obtained by primers specific for F. avenaceum and F. culmorum, respectively. Five isolates F12 - F15 and F17 were identified as Fusarium sambucinum on the basis of cultural and morphological characters only which needs further investigations. All the isolates were tested for the pathogenicity on asymptomatic potato tubers of cv. Kufri Pukhraj at two different temperatures i.e. 4°C and 10°C. F. culmorum was found more virulent followed by F. avenaceum and F. sambucinum, causing significantly larger lesions at both 4°C and 10°C storage temperatures. Most virulent isolates of different Fusarium spp. were used to test disease reaction of six common cultivars of potato. Gautama cultivar was found highly susceptible to dry rot followed by Kufri Pukhraj.